2004
DOI: 10.1161/01.cir.0000133412.53089.26
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Carotid Artery Structure and Function in Children and Adolescents With Successful Renal Transplantation

Abstract: Background-Abnormal carotid artery compliance and increased intima-media thickness (IMT), markers of early atherosclerosis, are prevalent in adults with chronic kidney failure. However, little is known about the extent of these abnormalities in children after transplantation. Methods and Results-Thirty-one children (age, 14.5Ϯ4.1 years) with renal transplant (estimated glomerular filtration rate, 78.1Ϯ24.5 mL/min per 1.73 m 2 ; range, 44 to 128 mL/min per 1.73 m 2 ) and 33 age-and sex-matched control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
82
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 31 publications
13
82
2
Order By: Relevance
“…Mitsnefes and colleagues have reported that in children who have undergone renal transplants, systolic BP load was associated with decreased carotid artery distensibility. 14 The clinical significance of the differences in BP parameters between children with SDB and healthy controls is highlighted by the observed independent association between BP and left ventricular remodeling. We have previously demonstrated a greater relative wall thickness and left ventricular mass index in children with SDB as compared with children with simple snoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitsnefes and colleagues have reported that in children who have undergone renal transplants, systolic BP load was associated with decreased carotid artery distensibility. 14 The clinical significance of the differences in BP parameters between children with SDB and healthy controls is highlighted by the observed independent association between BP and left ventricular remodeling. We have previously demonstrated a greater relative wall thickness and left ventricular mass index in children with SDB as compared with children with simple snoring.…”
Section: Discussionmentioning
confidence: 99%
“…Among these measures are the rate of BP rise during the transition from sleep to wakefulness (referred to as morning BP surge), BP load, and diurnal and nocturnal BP measurements, all of which are important predictors of cardiovascular disease. [11][12][13][14][15] These parameters are known to be influenced by physical activity, degree of adiposity, and demographic characteristics. A rigorous comparison of these parameters in children with SDB and healthy controls that adjusts for these confounding factors has not, however, been performed.…”
mentioning
confidence: 99%
“…We and others have shown that endothelial dysfunction 24 and vascular damage [2][3][4][5][6] begin early in the course of CKD. The vascular damage is only partially reversible after transplantation 25 and use of lipid-lowering agents, 26 folate, 27 or arginine supplementation 28 has little effect. Goodman et al 29 and others 23 have shown that once a nidus of calcification forms in the soft tissues, "calcium begets calcium" such that patients with preexisting calcification are at greatest risk for accelerated calcification.…”
Section: Discussionmentioning
confidence: 99%
“…60 Mistnefes and coworkers confirmed these findings in a recent study. 61 In their study, these markers of atherosclerosis were associated with higher mean systolic blood pressures taken within 1 year before the study, higher daytime systolic blood pressure load (via ambulatory blood pressure monitoring), number of kidney transplants, and deceased-donor transplants. 61 These observations show that pediatric kidney transplant recipients might be at an increased risk for accelerated atherosclerosis and premature cardiovascular disease that strongly correlate with systolic blood pressure, deceased-donor donation, and the duration of renal replacement therapy.…”
Section: Introductionmentioning
confidence: 90%
“…[1][2][3] It represents a strong predictor of renal and patient cardiovascular outcomes 1,3,5,6,8,[11][12][13]15,17,35,56,58,[60][61][62][63] ( Figure 2). Therefore, posttransplant hypertension represents a multipathogenic process that amplifies a vicious cycle where allograft and cardiovascular outcomes in kidney transplant recipients are determined by the interaction of 2 distinct donor and recipient genetic make-ups, and the inherited cardiovascular and renal risk factors from earlier phases and new recipient and donor-related environmental and demographic variables that may occur during implantation and posttransplant (Figure 1).…”
Section: Introductionmentioning
confidence: 99%